Philadelphia, June 1876 Paper - The Mineral Wealth of Japan - Henry S. Munroe (The American Institute of Mining, Metallurgical, and Petroleum Engineers)
The earliest accounts we have of Japan represent the country as having great mineral wealth, especially of precious and useful metals. Marco Polo, the Venetian traveller, in the thirteenth century, writes of "Zipangu:" " They have gold in greatest abundance, its sources being inexhaustible. The king does not allow of its being exported. To this circumstance we are to attribute the extraordinary richness of the sovereign's palace. The entire roof is covered with a plating of gold.. .. The ceilings of the halls are of the same precious metal; many of the apartments have tables of pure gold of considerable thickness, and the windows also have golden ornaments." Marco Polo also gives an account of an unsuccessful Tartar expedition against Japan, prompted by the supposed great wealth of the country. Columbus also, as well as many other explorers, were attracted and encouraged by these prevalent reports of the wealth of the islands of Zipangu. Kaempfer, writing in 1727, speaks of the great mineral wealth of Japan, and especially of the abundance of gold, which, he says, is found in many provinces. The Portuguese and Dutch, while they had trading-posts in Japan, furnished tangible evidence of the truth of the early reports. Between 1550 and 1639 the Portuguese merchants sent home from Japan nearly three hundred million dollars' worth of bullion, most of which was gold. As the relative value of equal weights of gold and silver was then six to one, while in Europe, at the same time, it was nearly twelve to one, the exchange of silver bullion for gold was by no means an unimportant part of their Business. After the Portuguese, the Dutch continued the exportation of bullion, and the exchange of silver for gold, though with less profit, as the relative value of gold increased with the demand. Between 1649 and 1671 the Dutch traders sent home over two hundred million dollars in bullion, of which, however, nearly two-thirds was silver. In 1671 the Japanese government, alarmed at the rapid rate at which the precious metals were leaving the country, issued an edict forbidding the exportation of gold or silver, under heavy penalties, which had the immediate effect of stopping this trade. Besides bullion, copper formed at this time a most important article of export. According to Dr. Geerts,* who has examined the old